The magnitude of oral rehydration salt utilization in diarrhea hot spot regions of Ethiopia and its associated factors among under-five children: A multilevel analysis based on Bayesian approach - Negesse, Yilkal; Fetene Abebe, Gossa; Addisu, Abebaw; Setegn Alie, Melsew; Alemayehu, Dereje (Frontiers in Public Health, 2022)
Background: Diarrhea leads the children to severe dehydration or death as a result of the loss of water and electrolytes (potassium, chloride, sodium, and bicarbonate). To compensate for the losses, ORS is given to children who experienced diarrhea. Objective: To estimate the magnitude of ORS utilization in diarrhea hot spot regions of Ethiopia and to assess its associated factors among under-five children. Methods: To conduct this study we used the 2016 Ethiopian demographic and health survey data. A total of 1079 weighted sample children were selected. Each sample were selected randomly. Then to identify factors associated with ORS utilization in diarrhea hot spot regions of Ethiopia, multilevel analysis based on the Bayesian approach was applied. Finally the credible interval of AOR that doesn’t included 1 was considered statistically significant Results: The magnitude of ORS utilization for children in diarrhea hot spot regions of Ethiopia was 28%. Being urban resident (AOR=1.92; 95%CrI 1.13 – 3.3), female household head (AOR =2.11; 95% CrI 1.3 -3.9), having higher educational level (AOR=1.52; 95% CrI 1.04- 2.22), member of health insurance (AOR=1.73; 95%CrI 1.14 – 2.43), and being exposed for media (AOR=1.43; 95% CrI 1.18- 2.5) increases ORS utilization for diarrhea management. Conclusion: Residence, educational level, health insurance and media exposure were factors of ORS utilization. So, to increase the practice of ORS utilization for diarrhea management in Ethiopia, the ministry of health and the government of Ethiopia should consider those factors when they design diarrhea prevention and control strategies.